Kepemimpinan Perempuan di Lembaga Pendidikan Islam Kontemporer: Antara Normativitas Agama dan Tuntutan Kesetaraan Gender - Muhalli; Ahmad Sulhan; Mira Mareta; Maimun (Mataram University, 2026)
Female leadership in Islamic educational institutions currently stands at a crossroads between the demands of global modernization and the resistance of traditional religious interpretations. This phenomenon triggers a long-standing debate regarding the extent to which authority can be granted to women without infringing upon the boundaries of religious normativity. This article critically examines the phenomenon of female leadership in contemporary Islamic educational institutions by analyzing the dialectical tension between historically inherited religious normativity and the growing demands for gender equality in both global and national discourses. Employing a critical-hermeneutic approach to religious texts alongside a multidisciplinary literature review, this study maps three primary arenas of debate: (1) classic fiqh interpretations versus contextual reinterpretations regarding female leadership; (2) the empirical reality of female leadership in madrasahs, pesantrens (Islamic boarding schools), and Islamic higher education institutions; and (3) the structural-cultural barriers that restrict the actualization of female leadership despite the absence of absolute theological prohibitions. The findings indicate that obstacles to female leadership in Islamic educational institutions stem predominantly from patriarchal socio-cultural constructions embedded within religious interpretations rather than from Islamic doctrine itself. The maqashid al-shari'ah approach which emphasizes justice and public interest along with the contextual hermeneutics developed by Muslim feminists such as Amina Wadud and Nasaruddin Umar, offers a robust theological foundation to legitimize female leadership. This article concludes that the transformation of female leadership in Islamic educational institutions requires simultaneous reforms: hermeneutical (recontextualization of interpretations), structural (affirmative institutional policies), and pedagogical (gender-based leadership curricula).